(untitled) (International Journal of Nursing Education, 2020)
Background: Chronic kidney disease affected 753 million people globally in 2016, including 417 million females and 336 million males.1 So it is important to enhance the knowledge and practice regarding nursing management of patient during hemodialysis among staff nurses. Method: Quantitative research approach with pre-experimental one group pre-test and post-test design was adopted and sample was selected by using non-probability convenience sampling technique which consists of 90 samples. Aself-structured knowledge questionnaires and practice checklist was prepared to assess the knowledge and practice of staff nurses. Result: With regards to the pre-test knowledge, the score of 19 (21.1%) staff nurses had adequate level of knowledge and 71(78.9%) had inadequate knowledge, while in post-test 80(88.9%) had excellent knowledge, 4(4.4%)had inadequate level of knowledge and 6(6.7%) of them had adequate knowledge. The obtained pretest mean score was 8.61 and after providing SOP it increased to 13.83, the mean difference of the pre-test and post-test was 5.22. The standard deviation (SD) of pre-test & post-test was 35.99 & 18.8. The obtained paired “t” test value was 43.57, significant at 0.05 level. Whereas the pre-test score of practice shown 51 (56.67%) had inadequate practice and 39 (43.33%) had adequate practice, the post-test data reveals that 80 (88.9%) had excellent score towards practice. The obtained pre-test practice of mean score was 8.68 and post-test of practice mean score was 13.88 of staff nurses. The mean difference of the pre test and post test of practice score was 5.2 the pre-test SD of practice score was 0.89 and post-test SD 0.79 the obtained paired ‘t’ test value 45.11, shows significant at 0.05 level. It indicates that there was increased in the level of knowledge and practice towards nursing management of patient during hemodialys is after providing SOP. Conclusion: The findings of the study concluded that majority of staff nurses were having inadequate level of knowledge and average practice. The SOP was effective among staff nurses in improving knowledge (t (89) = 43.57) and practice score (t (89) =45.11) significant at 0.05 level regarding nursing management of patient during hemodialysis.